A call to improve educational programs in strength and conditioning - Massey, C. D.; Maneval, M. (Strength and Conditioning Journal, 2014)
The objective of this article is to merge a qualitative-descriptive research approach with the insights of others' knowledge about the field of strength and conditioning to determine the essential qualifications, prerequisites, and skills to function and excel within the profession. From this analysis, recommendations are made concerning future training and educational preparation of prospective strength and conditioning coaches. The strength and conditioning of athletes is described primarily as a coaching function with a need to focus more on the sport sciences in our educational curriculums as opposed to those based in exercise science.